Accurate estimation of the probability of observing a reactor to the skin test in officially tuberculosis free herds in a high prevalence region - Alberto Gomez-Buendia; Javier Ortega; Alberto Diez-Guerrier; Javier Bezos; Beatriz Romero; Julio Alvarez (The Veterinary Journal, 2026)

Revisiting Mycobacterium bovis SB0121 genetic diversity reflects the complexity behind bovine tuberculosis persistence in Spain - Víctor Lorente-Leal; Pilar Pozo; Javier Bezos; Soledad Collado; Joaquín Vicente; Tod Stuber; Julio Álvarez; Lucía de Juan; Beatriz Romero (Preventive Veterinary Medicine, 2025)

Immunological mechanisms involved in the protection against development of pulmonary tuberculosis in naturally infected goats - Irene Agulló-Ros; Rita Vaz-Rodrigues; Mercedes Domínguez; Álvaro Roy; Javier Ortega; Inmaculada Moreno; Javier Bezos; Lucas Domínguez; Isabel G. Fernández de Mera; María A. Risalde (Veterinary Microbiology, 2025)

Evaluating the ability of non-tuberculous mycobacteria to induce non-specific reactions in bovine tuberculosis diagnostic tests in guinea pigs and cattle - Alberto Gomez-Buendia; Javier Ortega; Alberto Diez-Guerrier; Aaron Rendahl; Jose Luis Saez; Javier Bezos; Beatriz Romero; Julio Alvarez (Veterinary Microbiology, 2024)

Once bitten twice shy: Risk factors associated with bovine tuberculosis recurrence in Castilla y Leon, Spain - Pilar Pozo; Javier Bezos; Beatriz Romero; Anna Grau; Jesus Nacar; Jose Luis Saez; Olga Minguez; Julio Alvarez (Research in Veterinary Science, 2023)

Extracellular matrix proteins (fibronectin, collagen III, and collagen I) immunoexpression in goat tuberculous granulomas (Mycobacterium caprae) - Carlos Neila; Agustín Rebollada-Merino; Javier Bezos; Lucía de Juan; Lucas Domínguez; Antonio Rodríguez-Bertos (Veterinary Research Communications, 2022)
The lesion resulting from the interaction between Mycobacterium and the host immune response is the tuberculous granuloma. Tuberculous granulomas, except in incipient stages, are partially or totally encapsulated by connective tissue. The aim of this study was to assess the immunoexpression of the extracellular matrix proteins fibronectin, collagen III, and collagen I in granulomas caused by Mycobacterium caprae in goats ( Capra aegagrus hircus ) to understand capsule development at different granuloma stages. For this purpose, a retrospective study of 56 samples of tuberculous granulomas in lung ( n = 30) and mediastinal lymph node ( n = 26) from 17 goats naturally infected with M. caprae in stages I ( n = 15), II ( n = 14) and III ( n = 27) was carried out. Fibronectin immunoreaction was extracellular, fibrillar-reticular in the center of stage I, II and III granulomas and peripheral in stages II and III granulomas. Collagen III immunoexpression was extracellular and fibrillar in the center of stages I, II and III tuberculous granulomas in lung and mediastinal lymph node, and progressive expression was observed in the periphery of stages II and III granulomas. Finally, collagen I immunoexpression was extracellular and fibrillar, showing a progressive loss of central expression and an increase in peripheral expression in stage III granulomas compared to stage I granulomas. Immunoexpression of these extracellular matrix proteins could help understand fibrogenesis and dating in tuberculous granuloma in both animal models and humans.